Paradise Lost Thrice: Exile and the Abrahamic Religions in Aciman, Werfel, and Ashour - Hosny, Malak K (AUC Knowledge Fountain, 2025)
Exile is an integral part of the history of all three Abrahamic religions: Judaism, Christianity and Islam. This thesis compares between literary narratives of the exile of Jews, Christians, and Muslims. It explores the notion that having been exiled from Eden with the fall of Adam and Eve, and having each religion’s prophet’s story intrinsically tied with exile, the believers’ exile is then the third in a layered cycle of exile. Having lost the paradise, believers tend to search for earthly paradises that they attach themselves to, and then tragically lose those as well. The thesis’ three primary literary texts are: 1) Out of Egypt, a memoir by André Aciman which narrates the exile of Jews from Alexandria in the 20th century, 2) The Forty Days of Musa Dagh, a novel by Franz Werfel which captures the exile of Armenian Christians from Turkey during World War I, and 3) Granada: The Complete Trilogy, a trilogy by Radwa Ashour that tells the story of the exile of Arab Muslims from Al-Andalus during the 15th century. The thesis, methodologically using postcolonial theory and discourse analysis, investigates how the earthly paradise is created and lost, looks comparatively at how the different faiths affect the ways by which the characters resist exile, analyzes how linguistic tools, such as diglossia and codeswitching, are used as tools of resistance, and traces Odyssean echoes throughout the exilic narratives. This thesis addresses a research gap in interfaith research when it comes to the theme of exile. Its utilization of literary medium is also rare in this research field. Its significance lies in how this literary juxtaposition allows for a contrapuntal reading that sheds light on similarities and differences, of all the aforementioned elements, between the narratives of exiled Jews, Christians, and Muslims.